THE DETERMINANTS OF CAPITAL STRUCTURE: THE CASE OF VIETNAM - Nguyen, Thac Thanh Quyen (2018)
This dissertation explores the determinants of capital structure of listed Vietnamese firms as representative of an emerging market in Asian Pacific region which has a rapid economic growth. In the paper, I use the Vietnamese annual firm-specific data collected from Bloomberg database from 2006 to 2017 and employ the fixed effects model to investigate the relationship between determinants and firms’ leverage. From the result of the regression model, I conclude that profitability, non-debt tax shield, liquidity and share price performance all have significant negative effect on managers’ decision of debt financing whereas tangibility, firm size, growth opportunities and earnings volatility provide mixed results.